Criminal Penalties for Foreigners Engaged in Illegal Fishing Indonesia's ZEE Impact SDGs - Irawan, Aris; Asneliwarni; Julian Ransangan; Rachel Georghea Sentani (Lembaga Contrarius Indonesia, 2025)
This research examines Indonesia's criminal law policy's readiness to address fisheries and maritime crimes within the Indonesian Exclusive Economic Zone (ZEEI) and its implications for achieving the Sustainable Development Goals (SDGs). However, in the UNCLOS 1982, Indonesia is prohibited from imposing imprisonment as a sanction for violations of the ZEEI, allowing only fines as penalties. In addition to normative issues, structural issues also pose challenges to effective law enforcement and threaten the success of Indonesia's SDGs in the fisheries sector. Using a normative legal research method with statutory, conceptual, and historical approaches. The study finds that Indonesia, as a signatory to UNCLOS 1982, must carefully adapt international rules into national laws without compromising its sovereignty. To achieve legal certainty, imprisonment as an alternative to fines should be considered. Fisheries crimes in ZEEI negatively impact SDGs by depleting fishery resources, destabilizing the economy, violating human rights, and causing environmental damage. Judges play a critical role as enforcers of legal certainty and protectors of Indonesia's national interests through the Judicial Power Law. This research underscores the need for legal reform to strengthen Indonesia’s sovereignty and sustainability in maritime law enforcement.